2018
DOI: 10.1080/23273798.2018.1549332
|View full text |Cite
|
Sign up to set email alerts
|

Look and listen! The online processing of Korean case by native and non-native speakers

Abstract: Progamme. The views expressed here are those of the authors and not necessarily those of the funding agencies. The funders had no role in the study design, data collection and analysis, decision to publish, or preparation of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 50 publications
8
37
0
Order By: Relevance
“…Relatedly, studies on case marking have shown that comprehenders of German, Turkish, English, Korean, Hindi, and Japanese can use case-marked noun phrases to anticipate constituents that are yet to be mentioned (Frenck-Mestre et al, 2019;Henry et al, 2017;Hopp, 2015;Husain et al, 2014;Kamide, Scheepers, et al, 2003;Mitsugi & MacWhinney, 2016;Özge et al, 2016;Zhang & Knoeferle, 2012). Together, this evidence highlights a key role of morphosyntactic relationships in sentence comprehension: They allow speakers to proactively identify possible heads of noun phrases (gender and number agreement) and to assign thematic roles to these phrases (case marking), thus enabling incremental interpretation and enhancing comprehension speed and robustness to noise.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, studies on case marking have shown that comprehenders of German, Turkish, English, Korean, Hindi, and Japanese can use case-marked noun phrases to anticipate constituents that are yet to be mentioned (Frenck-Mestre et al, 2019;Henry et al, 2017;Hopp, 2015;Husain et al, 2014;Kamide, Scheepers, et al, 2003;Mitsugi & MacWhinney, 2016;Özge et al, 2016;Zhang & Knoeferle, 2012). Together, this evidence highlights a key role of morphosyntactic relationships in sentence comprehension: They allow speakers to proactively identify possible heads of noun phrases (gender and number agreement) and to assign thematic roles to these phrases (case marking), thus enabling incremental interpretation and enhancing comprehension speed and robustness to noise.…”
Section: Introductionmentioning
confidence: 99%
“…The number of case markers in Korean is known as eight, including nominative, accusative, genitive, dative, locative, instrumental, comitative, and vocative. These case markers enable Korean to be flexible in the ordering of subject and object arguments as in Japanese, Turkish, or German [80].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, research on L2 learners has generally revealed a lesser capacity to process morphosyntactic markers online, either to compute structure or to predict upcoming elements [ 5 , 7 ]. Studies that have examined auditory sentence processing have shown dramatic differences between native speakers and L2 learners as concerns their ability to process grammatical case incrementally across several languages, including Korean [ 8 ], German [ 5 ], and Japanese [ 6 ]. During reading, differences between native speakers’ abilities and those of L2 learners are often observed, but to a lesser extent than during auditory processing of utterances [ 9 , 10 , 11 ], an issue that we address in the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…While both monolingual children and adults of case-marking languages are sensitive to case for predictive processing in non canonical word order (e.g., scrambling), they use a range of top-down and bottom-up cues. In contrast, bilingual children and adults rely more on word order, often misparsing structures in a non-canonical order [ 8 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%